The Impact of Menstrual Cycle Phases on Athletic Performance: A Comprehensive Review - Dominika Rosińska-Lewandoska; Dominika Lewandowska; Julia Ufnal; Anna Podraza; Dominika Strep; Julia Grabowska; Maciej Kwiatkowski; Patryk Romańczyk; Julia Białczak; Weronika Kanownik (Journal of Education, Health and Sport)
Introduction